2018
DOI: 10.1007/s10822-018-0151-9
|View full text |Cite
|
Sign up to set email alerts
|

SAMPL6 host–guest blind predictions using a non equilibrium alchemical approach

Abstract: In this paper, we compute, by means of a non equilibrium alchemical technique, called fast switching double annihilation methods (FSDAM), the absolute standard dissociation free energies of the the octa acids host-guest systems in the SAMPL6 challenge initiative. FSDAM is based on the production of canonical configurations of the bound and unbound states via enhanced sampling and on the subsequent generation of hundreds of fast non-equilibrium ligand annihilation trajectories. The annihilation free energies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 58 publications
(64 reference statements)
0
66
0
Order By: Relevance
“…These good performances of the NEW approach have been confirmed in the second round of the SAMPL6 challenge for the LogP. 21 In spite of the fact that the rare applications of NEW methods have been quite successfully for solvation and binding free energies of complex molecular systems, [32][33][34][35][36][37][38][39] the vast majority of practitioners still rely upon FEP-based technology, in most cases systematically and incautiously underrating the sampling issue. 26 This is probably due to incomplete or far-stretched analysis studies 31,40 where NEW methods have been shown, in specific examples, to be computationally comparable to or less efficient than equilibrium approaches.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These good performances of the NEW approach have been confirmed in the second round of the SAMPL6 challenge for the LogP. 21 In spite of the fact that the rare applications of NEW methods have been quite successfully for solvation and binding free energies of complex molecular systems, [32][33][34][35][36][37][38][39] the vast majority of practitioners still rely upon FEP-based technology, in most cases systematically and incautiously underrating the sampling issue. 26 This is probably due to incomplete or far-stretched analysis studies 31,40 where NEW methods have been shown, in specific examples, to be computationally comparable to or less efficient than equilibrium approaches.…”
Section: Resultsmentioning
confidence: 99%
“…NEW approaches are still rarely used in free energy calculations. In the recent SAMPL6 initiative for blind prediction of host-guest binding free energies 25 , the only NEW submission 39 turned out be one of the best performing methods in the challenge. These good performances of the NEW approach have been confirmed in the second round of the SAMPL6 challenge for the LogP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical assessment of the modeling (SAMPL) challenges feature the assessments of the sampling and Hamiltonian issues in the computational modeling of solvation free energies, pKa, host-guest systems, partition coefficients, and protein-ligand binding. [90][91][92][93][94][95] The host-guest systems are analogues of protein-ligand complexes. They are smaller and simpler than proteins and ligands.…”
Section: Introductionmentioning
confidence: 99%
“…92,95 Nonequilibrium free energy simulations in the alchemical space were performed to calculate the host-guest binding affinities. 94 Although the free energy methods are accurate, the mean deviations from the experimental reference are often 2 kcal/mol, 93 which in principle arise from the Hamiltonian issue.…”
Section: Introductionmentioning
confidence: 99%